Drift demands of low-ductile moment resistance frames (MRF) under far field earthquake excitations - Vafaei, M. (Penerbit UTM Press, 2016)
Most of current Malaysian’s structures have not been designed with consideration of seismic excitation effect. Tremors that have been recorded locally due to active local faults and earthquake events in neighboring countries have raised the question about the level of safety of these structures. The effects of seismic excitation on the stability and fragility of the structures are now being concerned by most researchers and engineers in order to mitigate structural damage and societal losses. This study focuses on the seismic performance of Reinforced Concrete (RC) Moment Resistance Frames (MRF) in Malaysia which has been only designed to resist gravity and wind loads effects. An ordinary building layout with different number of stories (four, seven, and 10 stories) is selected in a way that can represent the potential of soft-story phenomenon in RC buildings in Malaysia. Such structures have limited lateral load capacity to withstand against strong ground motion. Nonlinear time history analysis is used to analyze the structures using seven different ground motions scaled to 0.05g, 0.1g and 0.15g to suit Malaysian condition. The outcomes of this study illustrate the vulnerability of the typical RC, MRF structures in Malaysia to soft-story phenomenon and clarify on the necessity of seismic retrofit for such structures.